Organised Resistance, Terrorism and Criminality in Ireland: The State's Construction of the Control Equation - FINDLAY, Mark (Institutional Knowledge at Singapore Management University, 1984)
Despite the reality of partition that created "two Irelands," comparative analysis of the state's reactions to terrorism in the Province and in the Republic is rare. The struggle over reunification, which permeates society on both sides of the border, is usually viewed by the populist press not from the Irish viewpoint, but rather from the perspective of the British government. Given this bias, organized resistance -- most notably in the North of Ireland -- is represented as an assault on a majority-supported state. Because the legitimacy of the state under attack is rarely questioned, and the motivations for the resistance are over-simplified and misrepresented, the state's reaction to such terrorism escapes criticism, except in the most obvious instances.